2020
DOI: 10.1016/j.actbio.2019.11.052
|View full text |Cite
|
Sign up to set email alerts
|

Sustained low-dose dexamethasone delivery via a PLGA microsphere-embedded agarose implant for enhanced osteochondral repair

Abstract: Articular cartilage defects are a common source of joint pain and dysfunction. We hypothesized that sustained low-dose dexamethasone (DEX) delivery via an acellular osteochondral implant would have a dual pro-anabolic and anti-catabolic effect, both supporting the functional integrity of adjacent graft and host tissue while also attenuating inflammation caused by iatrogenic injury. An acellular agarose hydrogel carrier with embedded DEX-loaded poly(lactic-co-glycolic) acid (PLGA) microspheres (DLMS) was develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 78 publications
0
55
0
Order By: Relevance
“…PLGA is hydrolyzed into lactic acid and glycolic acid in vivo, and further metabolized into water and carbon dioxide through the tricarboxylic acid cycle, and finally excreted in the lung. The safety of PLGA has been recognized by the United States Food and Drug Administration(FDA) and the European Medicines Agency, and has now been officially included by the FDA as a pharmaceutical excipient (Han et al, 2016;Ruman et al, 2020;Stefani et al, 2020). The properties of PLGA can be changed by adjusting the monomer ratio (LA/GA), molecular weight (M W ), concentration, and terminal group, which will affect the encapsulation efficiency (EE%) and drug release kinetics of PLGA microspheres (Li et al, 2021).…”
Section: Plga As Biodegradable Microsphere Carrier Materialsmentioning
confidence: 99%
“…PLGA is hydrolyzed into lactic acid and glycolic acid in vivo, and further metabolized into water and carbon dioxide through the tricarboxylic acid cycle, and finally excreted in the lung. The safety of PLGA has been recognized by the United States Food and Drug Administration(FDA) and the European Medicines Agency, and has now been officially included by the FDA as a pharmaceutical excipient (Han et al, 2016;Ruman et al, 2020;Stefani et al, 2020). The properties of PLGA can be changed by adjusting the monomer ratio (LA/GA), molecular weight (M W ), concentration, and terminal group, which will affect the encapsulation efficiency (EE%) and drug release kinetics of PLGA microspheres (Li et al, 2021).…”
Section: Plga As Biodegradable Microsphere Carrier Materialsmentioning
confidence: 99%
“…However, these materials are limited in terms of processability and manipulatable degradation time ( Pati et al, 2014 ). In contrast, synthetic polymers have good mechanical strength, controllable degradation and high plasticity ( Li et al, 2019b ; Stefani et al, 2020 ). But they also have shortcomings, such as poor biocompatibility, acidic degradation products, low biological activity, hydrophobicity and limited interfacial integration with tissue ( Stocco et al, 2014 ; Park et al, 2018 ; Lin et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dex also has an anticatabolic effect on cartilage in vitro. Low concentrations of Dex were able to protect cartilage explants from TNF- α and high dosage suppressed GAG content loss [ 29 ]. Black et al suggested in IL-1 α -stimulated bovine cartilage explants that Dex treatment largely inhibited transcriptions of IL-6, MMP-3, and MMP-13 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%